A Rolewicz-type characterization of nonuniform behaviour. Issue 14 (26th October 2021) - Backes, Lucas; Dragičević, Davor
ABSTRACT: We present necessary and sufficient conditions in the spirit of Rolewicz under which all Lyapunov exponents of a given linear cocycle are either positive or negative. As a consequence, we formulate new conditions for the existence of the so-called tempered exponential dichotomies. We consider cocycles over both maps and flows.